(untitled) (Archives of Mechanics - Test, 2000)
Effect of fiber treatment on the bending strength of the aramid short fiber composite is studied in this paper. Interfacial shear strength and fiber strength are determined for different fiber treatments by performing single-fiber pull-out test. Effect of the fiber treatments on the property of the composite depends both on the interfacial shear strength and the fiber strength, simultaneously. Thus, to evaluate quantitatively the effect of the treatments on the strength of the composite a parameter "critical embedded length" is introduced that covers both the interfacial shear strength and the fiber strength. It is a parameter that defines the maximum embedded length during pull-out test, above which the shear force in the fiber/matrix interface exceeds the value of fracturing force of the fiber. The result shows that decrease of the critical embedded length causes increase in the bending strength of the composite, for the cases of the treatments employed in this research. Finally, an empirical equation is developed to calculate the bending strength of the aramid short fiber composite for the fiber treatments employed in this research.